Organ donation and transplantation in the Russian Federation in 2022. 15th Report from the Registry of the Russian Transplant Society - S. V. Gautier; S. M. Khomyakov (Вестник трансплантологии и искусственных органов)
Objective: to monitor the current trends and developments in organ donation and transplantation in the Russian Federation based on data from the year 2022.Materials and methods. Heads of organ transplant centers were surveyed through questionnaires. Data control was done using the information accounting system of the Russian Ministry of Health. We performed a comparative analysis of data obtained over years from various federal subjects of the Russian Federation and transplant centers.Results. Based on data retrieved from the National Registry in 2022, 46 kidney, 31 liver and 16 heart transplant programs were existing in the Russian Federation as of the year 2022. Organ donation activity in 2022 was 5.2 per million population (p.m.p.), with a 73.7% multi-organ procurement rate and an average of 2.8 organs procured from one effective donor. In 2022, 2,555 organ transplants were performed in the Russian Federation, which included 1,562 kidney, 659 liver and 310 heart transplants. Same year, the number of transplant surgeries performed in the Russian Federation increased by 10.0% compared to 2021. In Moscow, organ donation activity was 26.3 p.m.p. The city of Moscow and the Moscow Oblast alone had a total of 12 transplant centers, accounting for 52.6% of all kidney transplants and 64.8% of all extrarenal transplants in the country. The number of organ recipients in the Russian Federation exceeds 150 p.m.p.Conclusion. The geographic distribution of transplant centers in the Russian Federation continues to expand. Five new centers were opened in 2022. Over the past year, the number of effective donors and organ transplants increased in the country. The resource potential of medical institutions has not been exhausted and this is set to further increase the number of organ transplants performed. Moscow is the powerhouse of Russian transplantology. However, other regional leaders have since appeared in the Russian Federation, such as in Kemerovo, Kazan, Rostov-on-Don, Tyumen, Irkutsk, and Volzhsky. In the Russian Federation, priority is being given to pediatric transplant care. It is expedient to implement a complex of measures aimed at identifying potential recipients.